Okultní aspekty v metalové hudbě: od hororového stylu k temné spiritualitě - Vrzal, Miroslav (Sacra, 2015)
In the last two decades, we can observe a trend that many metal bands have been accenting a serious interest in occult matter. As this article, reframing the history of metal music with respect to occult themes, argues, this trend started in the late '80s during the formation of extreme metal genres, especially black metal. In classical heavy metal, the occult topic was mostly based on a horror and fantasy discourse derived from the popular culture. The shift from heavy metal to extreme metal in the late ‘80s showed a different approach to using the occult as a topic in metal. For some extreme metal bands, the occult started to be an area of more serious interest. Thus, the occult dimension of metal has been more deeply connected with a milieu of dark spirituality.